Numerical analysis of hydrogen-assisted rolling-contact fatigue of wind turbine bearings (Fracture and Structural Integrity, 2014)
Offshore wind parks at locations further from the shore often involve serious difficulties, e.g. the maintenance. The bearings of offshore wind turbines are prone to suffer hydrogen-assisted rolling-contact fatigue (HA-RCF). Three important aspects linked with bearing failures are being extensively researched: (i) rolling contact fatigue (RCF), (ii) influence of carbide particles on fatigue life, and (iii) local microplastic strain accumulation via ratcheting. However, there is no reference related to bearing failure in harsh environment. This way, this paper helps to gain a better understanding of the influence of hydrogen on the service life of offshore wind turbine bearings through a numerical study. So, the widely used RCF ball-on-rod test was simulated by finite element method in order to obtain the stress-strain state inside the bearings during life in service and, from this, to elucidate the potential places where the hydrogen could be more harmful and, therefore, where the bearing material should be improved.
Keywords: Hydrogen-assisted rolling-contact fatigue